Memahami Konsep-Konsep Dasar Manajemen Strategis Sebagai Dasar Pengambilan Keputusan - Sinarwaty; Riska Y. Saputri; Sitti Ainun Soffijah S; Andi Ratu Alam (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
Strategic management is a fundamental element in determining the direction and sustainability of an organization amid the increasingly complex dynamics of the business environment. This journal aims to conduct an in-depth examination of the basic concepts of strategic management and its role as the primary foundation for organizational decision-making. The approach used is a qualitative descriptive study based on primary literature sources that discuss the concepts, stages, benefits, and challenges of strategic management. The results of the study indicate that strategic management does not only focus on long-term planning but also encompasses a continuous process involving the scanning of internal and external environments, strategy formulation, implementation, as well as evaluation and control. In the context of decision-making, strategic management helps organizations understand their current position, predict future conditions, and determine the most appropriate actions to achieve their goals. Furthermore, factors such as globalization and environmental sustainability increasingly reinforce the importance of strategic management as a tool for organizational adaptation. Thus, a solid understanding of the fundamental concepts of strategic management will enhance the quality of decisions made and support the organization’s long-term competitive advantage.